"A Substratum of Unprejudiced Art History": The critical discourse of Jewish art in early twentieth-century Germany. Issue 1 (2nd January 2016) - Straughn, Celka
Abstract : This essay investigates questions of Jewish art in early twentieth-century Germany, the motivations and contexts for such questions, and the methods used to understand them. Focusing on the 1907 "Exhibition of Jewish Artists" in Berlin and its critical reception as a primary case study, the essay grounds the discourse of Jewish art within its own particularities of production. It concludes with a brief analysis of the first major publication to present a history of Jewish art. The discourse of Jewish art in early twentieth-century Germany grappled with the challenges of determining a distinctly Jewish art using the tools of art history. Notions of Jewish artists and Jewish art, however, also presented challenges to the modernist structures of art history with its claims of secular universality and reason, exposing the contradictory assumptions of national and religious particularities.